Study on different anode/filter combinations and tube voltage values on image quality in mammography - Fairuz, Mohd Nasir; Nurul Syazwina, Mohamed; Nur Nazifah, Mohd Hashim (Penerbit Universiti Sultan Zainal Abidin, 2020)
The number of women around the world diagnosed with breast cancer is increasing every year. Mammography is the best equipment for the early diagnosis of breast cancer. Imaging the breast is challenging since there are only small differences in X-ray attenuation in the various breast soft tissue structures. Poor quality images reduce the detection rate of early breast cancer and the patient's chances of survival. Thus, this study aims to determine how the different anode/filter types and tube voltage values affect the image quality in mammography. Two different digital radiography systems of mammography were used. Firstly, using direct digital mammography (DDM) with Tungsten (W) as the anode, Rhodium (Rh) and Silver (Ag) as filters. Secondly, computed radiography (CR) mammogram system had been operated with Molybdenum (Mo) as both anode and filter to image the RMI 156 phantom replacing the human breast. The phantom was exposed using anode/filter combinations of Mo/Mo, W/Rh, and W/Ag, at the different tube kVp values of 24, 26, 28, 30 and 32 kV. The resultant image was evaluated by counting the number of test object visible in the image. The W/Rh anode/filter and low tube kVp values gave the best image quality in mammography as they increase the visibility of image details.